IMAM SYAFI’I DAN PEMIKIRAN SINTESISNYA; STUDI ANALISIS PEMIKIRAN IMAM SYAFII DAN PENGARUHNYA TERHADAP PERKEMBANGAN DISKURSUS KEISLAMAN (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
Imam Syafi'i schools including one of the founders of Islamic jurisprudence is very intelligent. No less than some of the treasures of Islamic scholarship controlled, ranging from classical fiqh thought, Kalam, politics (siyasa) Islam, study the Koran (Ulumul Qur'an), hadith. He left many works in various Islamic literature, his works about the prophetic narrations, and ar-Risalah which became the prototype book of philosophy of Islamic law (usulfiqh).Imam Syafi'i that ideas are very large, so the scholars classify him as a mujtahidmustaqil, the mujtahid who do not rely ijtihad to anyone. He is one mujtahid who has most followers throughout the history of Islam until today.The main basis of Imam Syafi'i foothold in setting madzhabnya is a balance between the synthesis and the establishment of a law based on the principles of textual (al-Qur'an and hadith) and the rules of the ratio (qiyas) .Sintesis generated by Imam Shafi'i was built based on some rules raw between the various theories of classical fiqh and its methodology to obtain a legal enactment. The aim is to find out which of those opinions that are closer to the truth and which are consistent with the objectives of sharia itself (maqashidshari'a).Imam Syafi’i, Thought synthesis